Discursos (des)valorizados sobre a avaliação: compreensão dos movimentos discursivos da ABMES e da Andifes no mercado linguístico das políticas públicas de avaliação da educação superior brasileira - Bernardes, Joelma dos Santos (2018)
This work aims to identify which were the political discourses of educational agents regarding the evaluation of higher education were articulated towards the evaluative State in the formulation of public policies of higher education evaluation in Brazil, in a period ranging from 1993 to 2010. By analyzing the scientific and academic literature dealing with public policies of higher education evaluation, 61 educational agents were identified, classified, and selected. They had interlocution and articulation, either directly or indirectly, with the evaluative State during the period of the research. After applying investigative criteria, the Brazilian Association of Maintainers of Higher Education (Associação Brasileira de Mantenedoras de Ensino Superior - ABMES), and the National Association of Directors of Federal Institutions of Higher Education (Associação Nacional dos Dirigentes das Instituições Federais de Ensino Superior - Andifes) were selected. The theoretical foundations of the research were grounded on Pierre Bourdieu's conceptual-interpretative appropriations of the linguistic market of the field of educational evaluation, as well as educational field and educational agent; and Guy Neave's evaluative State, reconfigured by Almerindo Janela Afonso constituted the theoretical-methodological reference of the research. The nature of the work was quanti-qualitative, being used as methodological procedures of data collection the bibliometric study, the bibliographical survey and the documentary research. The role performed by agents on the formulation and implementation of public evaluation policies were evidenced through the Program of Institutional Evaluation of the Brazilian Universities (Programa de Avaliação Institucional das Universidades Brasileiras - PAIUB), in 1993, as well as through the National Courses Exam (Exame Nacional de Cursos - ENC), in 1995, and the National System of Evaluation of the Higher Education (Sistema Nacional de Avaliação da Educação Superior - SINAES), in 2004. Educational agents negotiated political discourses, whether valued or devalued, during the period. Tensions and disputes were generated in the linguistic market of the field of educational evaluation, so that these discourses were recognized and legitimized in the social magic through regulation of policies of higher education evaluation. In the first years of SINAES, in which the university reform proposal was executed, ABMES and Andifes agreed that it would be a moment of appreciation of political discourses and changes of positions within the educational field. To do it, ABMES' discursive negotiations were carried out with the following utterances: "representativeness, evaluation, and regulation". In its turn, Andifes' utterances were "financing and institutional autonomy". It is concluded that, in the linguistic market of the field of educational evaluation, ABMES and Andifes negotiated their political discourses, which sometimes were unified in favor of an evaluation policy for the improvement of the quality of teaching, and sometimes opposed in the way the evaluation results should formulate educational and evaluative policies on how they could go over into the expansion of higher education by the public sector and the private sector. In this sense, there was the universal message within the linguistic market that evaluative policies would be indispensable for the expansion with quality of higher education, although there are different objectives for evaluation, expansion, and use of results among agents. In this way, discourses moved the linguistic market through symbolic and linguistic exchanges, aiming to obtain appreciation price (value) on the devaluation of the other.